From streets to screens: legal implications of internet begging - Hamzeh Abu Issa; Naji Al wreikat; Tareq Al-billeh; Tariq Alhasan (Humanities & Social Sciences Communications)
Abstract The evolution from traditional street begging to digital solicitation—referred to as internet begging—marks a significant shift in how individuals seek charitable assistance. This study employs a four‐pronged methodological approach: (a) a comprehensive literature review that identifies prevailing debates and research gaps; (b) a comparative legal analysis of regulatory frameworks in Jordan, the United Arab Emirates, and Egypt; (c) detailed case studies of judicial decisions illustrating enforcement practices; and (d) a policy analysis that formulates concrete recommendations. Our findings reveal that internet begging constitutes a distinct cybercrime. Specifically, it requires both actus reus and mens rea in order to meet the legal thresholds set out in Article 23 of Jordan’s Cybercrime Law No. 17 of 2023, which imposes penalties of six to twelve months’ imprisonment and fines from 3000 to 5000 dinars. The paper critically examines the implications of criminalizing digital solicitation by addressing the tension between preventing exploitation and considering the socioeconomic drivers that lead individuals to seek aid online. Furthermore, it explores how Islamic doctrines and cultural norms in Jordan and the broader Arab world shape legal responses. While international instruments provide frameworks for combating digital offenses, they do not explicitly regulate internet begging, thereby revealing a regulatory gap. This study fills that gap through a novel comparative legal analysis combined with a policy evaluation and offers actionable recommendations aimed at enhancing enforcement, promoting rehabilitation, and strengthening international cooperation. The implications of our findings extend to legal practitioners, policymakers, and scholars, providing a robust foundation for future legislative reforms to effectively regulate digital solicitation activities.